Advocacy for efficiency and renewal of the banking and financial system in Algeria - LAZREG, Mohammed; GODIH, Djamel torqui (Journal of Human Sciences, 2020)
The main objective of our article focuses on the financial and banking system that is a lever of action for economic development in Algeria. A central question is at the heart of our problem: What are the guidelines to be implemented for efficiency and a revival of the banking and financial system in Algeria? Our methodology is based on a theoretical approach on the one hand and an empirical approach on the other. To this end, we have highlighted a questionnaire relating to the appreciation of companies on the financing of economic activity in Algeria. Thus, the results obtained confirmed our theoretical approach as to the fundamental levers to be highlighted for efficiency and a revival of the banking and financial system in Algeria, these are among others: human resources, good governance and an economy based on knowledge....